Placental syndromes and maternal cardiovascular health - Casey, Helen; Dennehy, Natalie; Fraser, Abigail; Lees, Christoph; McEniery, Carmel M; Scott, Kayley; Wilkinson, Ian B; Delles, Christian (Clinical science (1979), 2023)
The placental syndromes gestational hypertension, preeclampsia and intrauterine growth restriction are associated with an increased cardiovascular risk to the mother later in life. In this review, we argue that a woman's pre-conception cardiovascular health drives both the development of placental syndromes and long-term cardiovascular risk but acknowledge that placental syndromes can also contribute to future cardiovascular risk independent of pre-conception health. We describe how preclinical studies in models of preeclampsia inform our understanding of the links with later cardiovascular disease, and how current pre-pregnancy studies may explain relative contributions of both pre-conception factors and the occurrence of placental syndromes to long-term cardiovascular disease.